Translation and Validation Study of the Persian Version of the Oxford Shoulder Instability Score - GholamReza Olyaei; SayedJavad Mousavi; Ali Montazeri; Kazem Malmir (Journal of Modern Rehabilitation, 2016)
Introduction: Assessing quality of life for patients with shoulder instability may be essential because of the negative impacts of the disease on patient’s life. The aim of the present study, therefore,  was  to  assess  the  internal  validity  and  consistency,  test-retest  reliability,  and convergent validity of the Persian version of the Oxford Shoulder Instability Score (OSIS). Material and Methods: A total of 150 patients with shoulder instability completed the Persian OSIS, Disabilities of the Arm, Shoulder, and Hand (DASH), and visual analog scale (VAS) to test convergent validity. 50 randomly selected patients completed the OSIS, 48 hours later, for the second time. Results: Cronbach’s alpha coefficient for the Persian OSIS was 0.90. The Persian OSIS showed excellent test-retest reliability with intraclass correlation coefficient 0.94 (P < 0.01). The Pearson’s correlation coefficient between the Persian OSIS and DASH and VAS was 0.84 and 0.79, respectively (P < 0.01), indicating a good convergent validity. Conclusion: The Persian OSIS is a reliable and valid instrument to measure health-related quality of life and functional disability in Persian-speaking patients with shoulder instability in Iran.